EFEKTIFITAS TERAPI AKUPRESUR PADA TITIK SP 6 (SANYINJIAO) DAN TERAPI SLOW STROKE BACK MASSAGE TERHADAP TEKANAN DARAH PADA LANJUT USIA - Made Indra Ayu Astarini; Ninda Ayu Prabasari; Kristo Marco Rumangun (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: to explain the effectivity of acupressure therapy at the SP 6 (sanyinjiao) point and slow stroke back massage therapy on blood pressure in the elderly with hypertension.Methods: This article used a pre-experimental research design with a one-group pretest-posttest design approach. The population of the study was 26 respondents aged 60 years who had hypertension at Privat Nursing Home in Surabaya. The sampling technique used purposive sampling, obtained a sample of 24 elderly who met the inclusion criteria.  These two therapies were carried out alternately for each patient. Therapy was given 6 times every two days. Test analysis used Paired T-test.Results: The average result of systolic pre-test blood pressure was 149.20 mmHg and diastolic pre-test was 94.58 mmHg, and the post-test systolic average result was 130.33 mmHg and diastolic blood pressure was 72.37 mmHg. Paired T-test blood pressure pre-test and post-test is p= 0.001 < α (0,05)  Conclusion: There is an effect of SP 6 acupressure therapy and Slow Stroke Back Massage therapy on blood pressure in hypertensive elderly. SP 6 acupressure therapy and slow stroke back massage therapy will release endorphins, thereby providing a sense of calm and comfort. This relaxation condition affects changes in blood pressure.